Assessment of biochemical liver markers, physical activity, fitness and body mass index for a cardiometabolic risk model in childhood. (13th March 2014) - Konidari, A; Auth, MKH; Murphy, MH; Cunningham, C; Foweather, L; Gobbi, R; Graves, LEF; Hopkins, ND; Stratton, G; Boddy, LM
Abstract Aim The aim of this study was to investigate clustered cardiometabolic risk scores in healthy 10‐ to 12‐year‐olds using anthropometric characteristics, measurements of cardiorespiratory fitness (CRF) and physical activity and blood markers of metabolic disease. We also evaluated how including markers of liver cell injury would affect the clustered cardiometabolic risk assessment model. Methods This cross‐sectional study focused on 99 children aged 10–12 years. The main outcome included assessing participants with increased and low cardiometabolic risk factors using a clustered risk score model that incorporated markers implicated in metabolic syndrome pathogenesis. Two clustered risk scores were calculated, one incorporating markers of liver cell injury. Results Children classified as 'increased risk' exhibited significantly lower CRF and higher body mass index Z‐scores than their 'low‐risk' peers. No significant differences in physical activity were observed. This trend remained unchanged when markers of liver injury were included in the clustered risk assessment model. Conclusion The clustered risk score model is a scientifically robust method of cardiometabolic risk assessment, which reiterates the importance of weight reduction and CRF promotion in childhood. Our study did not show a significant contribution of liver injury markers, and further research is needed to evaluate their effect on cardiometabolic risk stratification in childhood.